2012
DOI: 10.1016/j.micpath.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis entry into gingival epithelial cells modulated by Fusobacterium nucleatum is dependent on lipid rafts

Abstract: Host cell invasion by a major periodontal pathogen, Porphyromonas gingivalis, has been proposed as an important mechanism involved in host–pathogen interactions in periodontal and cardiovascular diseases. The present study sought to gain insight into the underlying mechanism(s) involved in previously demonstrated fusobacterial modulation of host cell invasion by P. gingivalis. An immortalized human gingival cell line Ca9-22 was dually infected with P. gingivalis ATCC 33277 and Fusobacterium nucleatum TDC 100, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 49 publications
3
40
1
Order By: Relevance
“…Capsulated Pg in mixed infection displayed a higher capacity for keratinocyte invasion than the non‐capsulated form, whereas elimination of coaggregation reduced capsulated Pg invasion. Also Saito et al 19 found mixed infection by Pg and Fn led to greater invasion of human keratinocytes by Pg (using the non‐capsulated ATCC 33277 strain). These changes may explain both the augmented virulence of mixed infection with capsulated Pg and also its attenuation once coaggregation is eliminated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Capsulated Pg in mixed infection displayed a higher capacity for keratinocyte invasion than the non‐capsulated form, whereas elimination of coaggregation reduced capsulated Pg invasion. Also Saito et al 19 found mixed infection by Pg and Fn led to greater invasion of human keratinocytes by Pg (using the non‐capsulated ATCC 33277 strain). These changes may explain both the augmented virulence of mixed infection with capsulated Pg and also its attenuation once coaggregation is eliminated.…”
Section: Discussionmentioning
confidence: 97%
“…These changes may explain both the augmented virulence of mixed infection with capsulated Pg and also its attenuation once coaggregation is eliminated. Saito et al 19 also reported that Pg invasion in mixed infection was not dependent on SerB, which is crucial for Pg invasion in the monoinfection mode. This highlights the finding that bacterial invasion in mixed infection relies on a mechanism specific to the mixed infection, and that unique interactions (such as coaggregation) may play a critical role in the virulence of mixed infection.…”
Section: Discussionmentioning
confidence: 98%
“…Intracellular bacteria disrupt host cell signaling pathways and gene expression patterns which can have profound effects on immune activity and cellular physiology [37]. Co-operative invasion among periodontal bacteria has been documented, for example consortia of P. gingivalis and F. nucleatum invade GECs in higher numbers than either organism alone [38]. Filifactor alocis and P. gingivalis also exhibit synergistic infection of epithelial cells and dual species invasion elicits a distinct pattern of host cell response [39].…”
Section: Interactions Between Bacterial Communities and Epithelial Cellsmentioning
confidence: 99%
“…gingivalis-induced Akt Inactivation Is Independent of P. gingivalis Invasion-P. gingivalis is capable of invading gingival epithelial cells and fibroblasts (13,42,43), and the virulence factors produced by P. gingivalis including outer membrane vesicles, which enter into host cells (44), and SerB, which is a serine phosphatase and contributes to P. gingivalis invasion (45), also interacts with host proteins in gingival epithelial cells. Lipid rafts are also involved in P. gingivalis invasion (42,46). To investigate whether Akt dephosphorylation is caused by invading P. gingivalis or endocytosed virulence factors, we employed CytD and MCD.…”
Section: P Gingivalis Induces Akt Inactivation and Subsequentmentioning
confidence: 99%